2014
DOI: 10.5812/iranjradiol.13262
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasound as a Screening Tool for Performing Caudal Epidural Injections

Abstract: Background:The caudal approach to the epidural space has been used for decades to treat low back pain caused by lumbosacral root compression. The use of fluoroscopy during epidural steroid injection is the preferred method for placing the needle more accurately in the sacral hiatus, but it carries the risk of radiation hazard.Objectives:The aim of the study was to assess the anatomical structure of the sacral hiatus and the feasibility of caudal epidural injections under ultrasound guidance.Patients and Method… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
32
0
4

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(39 citation statements)
references
References 21 publications
(33 reference statements)
3
32
0
4
Order By: Relevance
“…Several studies from various ethnic populations have repeatedly reported very high successful rates (96.9–100%) of ultrasound-guided caudal injection [11, 12, 2527]. The patient can be placed in prone or lateral decubitus position.…”
Section: Techniques Of Caudal Epidural Blockmentioning
confidence: 99%
“…Several studies from various ethnic populations have repeatedly reported very high successful rates (96.9–100%) of ultrasound-guided caudal injection [11, 12, 2527]. The patient can be placed in prone or lateral decubitus position.…”
Section: Techniques Of Caudal Epidural Blockmentioning
confidence: 99%
“…Klocke et al [27] were the first to describe a sonographic method for identifying the sacral hiatus landmarks to facilitate real-time guidance of steroid injections into the caudal epidural space. Nikooseresht et al [13] and Kim et al [14] presented in a similar setting that ultrasound can be used as a screening tool for performing caudal epidural injections. Quite recently Kao et al demonstrated in their review article relevant anatomic features and variations of the sacral bone and the development of imaging guided techniques, also including the US-guided approach for performing caudal epidural injections [15], They used a longitudinal transducer position with the sacrococcygeal ligament as the sighted landmark.…”
Section: Discussionmentioning
confidence: 99%
“…Different approaches have already been described for the cervical [11] and lumbar spine [12], proving the feasibility and effectiveness of US-guided injections in the spine. However, concerning the sacral spine, only a few reports can be found in the literature [13][14][15][16].…”
Section: Introductionmentioning
confidence: 99%
“…Namun, penggunaan rutin teknik ini terhalang berbagai pertimbangan seperti paparan radiasi, biaya, dan kebutuhan akan lokasi khusus. 7 Saat dibandingdengan fluoroscopy, ultrasonografi memiliki keuntungan yaitu lebih mudah untuk dipelajari, bebas dari radiasi sehingga lebih memungkinkan untuk dilakukan pada berbagai kondisi, kejadian kebocoran vaskular yang lebih rendah, dan tingkat keberhasilan tindakan yang lebih tinggi. Hal-hal tersebut menjadikan ultrasonografi lebih cepat dan lebih mudah digunakan untuk tindakan anestesi kaudal.…”
Section: Pembahasanunclassified
“…Hal-hal tersebut menjadikan ultrasonografi lebih cepat dan lebih mudah digunakan untuk tindakan anestesi kaudal. [7][8][9] Melakukan blokade kaudal dengan blind technique memerlukan pengetahuan anatomi yang baik untuk menentukan landmarks. Teknik ini dinilai cepat dan mudah untuk dilakukan, namun kelemahan teknik ini dapat terjadi komplikasi serius berupa kerusakan saraf oleh tusukan langsung.…”
Section: Pembahasanunclassified